2021
DOI: 10.1039/d1md00025j
|View full text |Cite
|
Sign up to set email alerts
|

Modulating β-arrestin 2 recruitment at the δ- and μ-opioid receptors using peptidomimetic ligands

Abstract: µ Opioid receptors agonists provide potent and effective acute analgesia; however, their therapeutic window narrows considerably upon repeated administration, such as required for treating chronic pain. In contrast, bifunctional µ/δ...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 69 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…Recently, Sharma et al reported the molecular docking of δOR complexed with the Leu-Enk derivative bearing the Tyr1-ψ[(Z)CF=CH]-Gly2 substitution using the crystal structure of PDB 6PT2 . 67 These two structures of the zwitterionic Leu-Enk bound to δOR were denoted as Docking1 and Docking2 in the present work, respectively, which were reoptimized at the SMD M06-2X/6-31+G(d) level of theory in water. In addition, Docking2 was reoptimized with the constraint of torsion angles ϕ 2 , ϕ 3 , ϕ 4 , and ϕ 5 fixed at the values of the corresponding structure of Leu-Enk bound to δOR at the same level of theory in water, which was denoted as Docking2-c.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Sharma et al reported the molecular docking of δOR complexed with the Leu-Enk derivative bearing the Tyr1-ψ[(Z)CF=CH]-Gly2 substitution using the crystal structure of PDB 6PT2 . 67 These two structures of the zwitterionic Leu-Enk bound to δOR were denoted as Docking1 and Docking2 in the present work, respectively, which were reoptimized at the SMD M06-2X/6-31+G(d) level of theory in water. In addition, Docking2 was reoptimized with the constraint of torsion angles ϕ 2 , ϕ 3 , ϕ 4 , and ϕ 5 fixed at the values of the corresponding structure of Leu-Enk bound to δOR at the same level of theory in water, which was denoted as Docking2-c.…”
Section: Resultsmentioning
confidence: 99%
“…However, the orientations of the side chain of the Phe4 residue and the carboxylate group of the Leu5 of the fully optimized conformer Docking2 were quite different from those of conformer Docking2 bound to δOR. 67 So, we located another conformer Docking2-c by the constrained optimization with four torsion angles ϕ 2 –ϕ 5 fixed at the values of conformer Docking2 bound to δOR. The values of Δ E w and Δ G w for conformer Docking2-c were 6.27 and 4.83 kcal mol –1 higher than those of the fully optimized conformer Docking2, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no explanation of how physicochemical properties modulated side effects. A recent study showed C -terminal amidated ENK reduced β-arrestin recruitment efficacies at MOR and KOR [ 247 ]. The role of the C -terminus is still not clear, due to the inconsistent results [ 60 ].…”
Section: Peptidomimetics For Opioid Receptorsmentioning
confidence: 99%
“…This insight has spurt efforts to develop G-protein-biased δOR agonists to reduce adverse effects including seizures, paralleling similar efforts for increasing the therapeutic window through G-protein-biased agonism at other GPCRs, including the µOR. These endeavors have generated a multitude of peptides with reduced β-arrestin recruitment potency/efficacy [ 3 , 32 , 33 , 34 , 35 ]. Similarly, small molecule biased agonists have also been developed including TAN-67, KNT-127, TRV250, and most recently PN6047.…”
Section: Introductionmentioning
confidence: 99%